The Efficacy of Isolated Bacteriophages from Pig Farms against ESBL/AmpC-Producing Escherichia coli from Pig and Turkey Farms - Skaradzińska, Aneta; Śliwka, Paulina; Kuźmińska-Bajor, Marta; Skaradziński, Grzegorz; Rząsa, Anna; Friese, Anika; Roschanski, Nicole; Murugaiyan, Jayaseelan; Roesler, Uwe H. (Frontiers in Microbiology, 2017)
Extended-spectrum β-lactamases (ESBLs) and AmpC β-lactamases are plasmid (but also chromosomally) encoded enzymes found in Enterobacteriaceae, determining resistance to a variety of important antibiotics including penicillins, cephalosporins, and monobactams. In recent decades, the prevalence of ESBL/AmpC-producing bacteria has increased rapidly across the world. Here, we evaluate the potential use of bacteriophages in terms of a reduction of antibiotic-resistant bacteria in healthy animals. The aim of our studies was to isolate bacteriophages capable of destroying ESBL/AmpC-producing E. coli isolated from livestock habitats. The efficacy of isolated phages against ESBL/AmpC E. coli strains varies, but creation of a phage cocktail with broad activity spectrum is possible. This may indicate that the role of phages may not be limited to phage therapy, but bacterial viruses may also be applied against spread of bacteria with antibiotic resistance genes in the environment. We also addressed the hypothesis, that phages, effective for therapeutic purposes may be isolated from distant places and even from different environments other than the actual location of the targeted bacteria. This may be beneficial for practical purposes, as the construction of effective phage preparations does not require access to disease outbreaks.